2010
DOI: 10.1002/jctb.2331
|View full text |Cite
|
Sign up to set email alerts
|

Silicone oil: An effective absorbent for the removal of hydrophobic volatile organic compounds

Abstract: International audienceBACKGROUND: Hydrophobic volatile organic compounds (VOCs), such as toluene, dimethyl sulfide (DMS) and dimethyl disulfide (DMDS), are poorly soluble in water and classical air treatment processes like chemical scrubbers are not efficient. An alternative technique involving an absorption step in an organic solvent followed by a biodegradation phase was proposed. The solvent must fulfil several characteristics, which are key factors of process efficiency, and a previous study allowed polydi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
85
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 124 publications
(89 citation statements)
references
References 14 publications
3
85
0
1
Order By: Relevance
“…6,7 As an alternative to the use of immiscible organic solvents several researchers have used low molecular weight poly(dimethylsiloxane), or silicone oil, as the sequestering phase, whose biocompatibility and non-biodegradability are advantages relative to many organic solvents. 8 While its low dielectric constant makes silicone oil well-suited for the extraction of hydrophobic solutes, its efficacy on more polar compounds is lacking, and its high cost makes it commercially unattractive. We have shown that inexpensive thermoplastics, usually in the form of small solid beads, can be used for a wide range of biosynthetic and biodegradative applications.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 As an alternative to the use of immiscible organic solvents several researchers have used low molecular weight poly(dimethylsiloxane), or silicone oil, as the sequestering phase, whose biocompatibility and non-biodegradability are advantages relative to many organic solvents. 8 While its low dielectric constant makes silicone oil well-suited for the extraction of hydrophobic solutes, its efficacy on more polar compounds is lacking, and its high cost makes it commercially unattractive. We have shown that inexpensive thermoplastics, usually in the form of small solid beads, can be used for a wide range of biosynthetic and biodegradative applications.…”
Section: Introductionmentioning
confidence: 99%
“…Silicone oil was selected since it is the most investigated NAP in TPPBs devoted to air pollution control [1,5]. In addition, silicone oil is, to the best of our knowledge, the only liquid NAP so far reported that is fully biocompatible, water immiscible and non-biodegradable [19,20].…”
Section: Two-phase Partitioning Bioreactormentioning
confidence: 99%
“…This list includes, 82 VOCs that have a vapor pressure ranging from 0.1 to 308 mmHg at 25°C. Since 125 3 Novel Bioreactors for Waste Gas Treatment then, several conferences such as New York (1997) and Kyoto (1998) highlighted the infl uence of anthropogenic VOC emissions on the environment and the climate imbalance (Darracq et al 2010 ) .…”
Section: Background Information On Air Pollutionmentioning
confidence: 99%
“…100% polydimethylsiloxane (PDMS) has unlimited useful life, very less volatility, high resistance to oxidation and exceptional stability to chemical attack. Silicone oil serves as the ideal candidate for use as an organic phase, in biological waste-gas treatment applications, due to the following advantages; (i) safe to use, (ii) high stability, (iii) non-toxic to the microorganisms, (iv) allows high pollutant solubility, which enables the treatment of high pollutant concentrations, (v) increases the specifi c interfacial area (gaseous) available for microorganisms to utilize the pollutant, by reducing the surface tension of water, (vi) controls the delivery pattern of the pollutant to the aqueous phase, (vii) enhances 149 3 Novel Bioreactors for Waste Gas Treatment oxygen mass transfer rates and (viii) positive impact on downstream operations, such as product recovery (Daugulis 1997(Daugulis , 2001Kennes and Veiga 2001 ;Bailón et al 2009 ;Montes et al 2009 ;Darracq et al 2010 ;Mahanty et al 2010 ) . It is important to add only low amounts of organic phase to the system, since that additional phase will also result in an additional cost.…”
Section: Typical Organic Solvents Used and Advantages Of Silicone Oilmentioning
confidence: 99%